Recent Progress toward the Construction of Axially Chiral Molecules Catalyzed by an N‑heterocyclic Carbene - Wang, Jiaming; Zhao, Changgui; Wang, Jian (ACS catalysis, 2021)
Axial chirality widely exists in natural products, pharmaceutical compounds, and other functional molecules; these axially chiral compounds also find wide utility as catalysts or ligands in organic synthetic chemistry. Nevertheless, whereas significant progress has been made toward the synthesis of enantioenriched axially chiral molecules over the past two decades, the strategies involving organocatalysis have only started to emerge recently. N-heterocyclic carbene (NHC) organocatalysts have been recognized to be powerful tools for the rapid construction of complex molecular architectures. However, previous works have mainly focused on the assembly of point chirality and only recently has it been realized that the asymmetric synthesis of axial chirality could be achieved by using NHCs as organocatalysts. This Perspective highlights the developments and advances in the synthesis of axially chiral scaffolds catalyzed by NHCs. The aim of this Perspective is to provide an overview of this area and serve as a stepping stone for future investigations.